Fiscal Policy Sustainability in Oil-Producing Countries - Bassett, Sheila (IMF Working Papers; Working Paper ;, 1994)
Assessing the sustainability of a given fiscal policy is especially important for countries that depend on income from exhaustible resources. Political and growth pressures may push governments to raise expenditure when revenue from exhaustible resources rises, but cutting outlays when price swings reduce income is often difficult. Traditional fiscal accounting may give a misleading view of policy sustainability. This paper argues that for countries in which a significant proportion of government revenue is derived from the exploitation of an exhaustible natural resource, fiscal policy sustainability can best be assessed within a permanent income framework that takes into account total government wealth, including the imputed wealth from reserves of natural resources. Using this framework, the paper takes a sample of six countries where government revenue from petroleum extraction is significant and draws conclusions about the sustainability of their fiscal policies during 1980-92.